Characterization of people seen at mental health clinics (Research, Society and Development, 2020)
The objective of the article was to identify the sociodemographic and clinical characteristics in the admission of adult patients treated by a multidisciplinary team in mental health outpatient clinics. Quantitative research conducted between January and March 2019, in four mental health clinics, in the city of Cuiabá, Mato Grosso, Brazil. In the 1780 medical records contemplated, the majority of users were female, between 30 and 39 years old, without partners, with little information about race / color, with diagnosis and use of psychiatric drugs prior to the first care performed by the doctor. 52.5% verbalized some type of previous medical diagnosis, the most frequent of which was depressive disorder 30.1%, followed by anxiety and eating disorders 20.4%. There is a relationship of mental suffering with the female gender and the centrality in medical work, even with the presence of a multidisciplinary team.